Do grassroots interventions relax behavioral constraints to the adoption of nutrition-sensitive food production systems? - Alvi, Muzna; Ward, Patrick S.; Makhija, Simrin; Spielman, David J. (Agricultural and Applied Economics Association, 2019)
In many developing countries, agricultural policies and programs are often designed in a way to promote productivity growth with modern inputs and technologies, and with limited reference to the nutrition gains that gain be made through production diversification. We test whether grassroots programs can relax behavioral constraints inhibiting the adoption of diversified nutrition-sensitive production systems. We use a series of labin-field experiments and survey instruments in Odisha, India to elicit male and female farmers’ preferences for risk, aversion to loss, empowerment and aspirations for one’s self and children. We find that respondents in villages where grassroots interventions were promoted showed significantly lower levels of risk aversion, higher levels of loss aversion and higher aspirations for themselves and their children, along with improvements in production and consumption diversity. Insights into the prevalence of behavioral constraints and interventions that relax such constraints fills an important knowledge gap in how to design programs that promote more nutrition-sensitive food production systems.